An economic and social history of the Netherlands, 1800-1920 : demographic, economic, and social transition - Wintle, Michael J. (Cambridge University Press, 2000)
This is a comprehensive account of Dutch history in the 'long' nineteenth century, examining population and health, the economy, and socio-political history. It is the only single-authored book available on this crucial period, and it will be of central importance to Dutch specialists, as well as European historians more generally.